ANALISIS KESESUAIAN AKAD WADIAHH PADA TABUNGAN HIJRAH HAJI DI BANK MUAMALAT KCU PALEMBANG - Anisah, Alya; Anisah Anandita, Alya; Hera, Putri; My Rahil (Kopertais Wilayah VII Palembang, 2024)
This study aims to analyze the compliance of the Wadiahh contract of the Hijrah Haji savings product of Bank Muamalat KCU Palembang with the principles of Sharia and applicable regulations. The research method used is qualitative with a case study approach. The data were collected through interviews, observations and documentary analysis. The results of the study show that the implementation of the Wadiahh contract in the Hijrah Haji Savings product is in line with Sharia principles. Bank Muamalat ensures that the funds deposited by customers are managed properly and can be returned at any time upon the customer’s request. According to Fatwa DSN-MUI No. 02/DSN-MUI/IV/2000 on Savings, this contract is permissible as long as the bank takes full responsibility for the return of the funds.